Presentación: Modelos económicos: Trade-off y comercio - Arzadun, Paula (My University, 2019)
La presentación explica los modelos de economía y se muestran diferentes representaciones simplificadas de la realidad, se proyecta la economía positiva frente a la economía normativa.

The presentation explains the economic models and shows different simplified representations of reality. The positive economy is projected against the normative economy.
Keywords: Microeconomía; Modelo económico; Ventaja comparativa; Economía positiva; Economía normativa; Costos; Costo de oportunidad; Empresas; Ciencias Administrativas; Microeconomics; Economic model; Comparative advantage; Positive economy; Normative economics; Costs; Opportunity cost; Business; Administrative Sciences